2016
DOI: 10.1021/acs.energyfuels.6b02457
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Kinetic Modeling Study of CH3OCH3 Ignition Sensitized by NO2

Abstract: We investigate the role of NO 2 in dimethyl ether (DME) ignition with a combustion shock tube. Ignition delay times are measured at 987−1517 K and 4 and 10 atm. Different equivalence ratios (0.5, 1.0, and 2.0) and NO 2 and DME concentrations are explored. NO 2 promotes DME ignition, and the promoting effect becomes more pronounced at high NO 2 concentrations or low temperatures. NO 2 addition also augments the influence of the equivalence ratio on ignition delay times. Four detailed reaction mechanisms from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…14 In Figure 7c, the calculated rate constants are compared with the values estimated by Xiao et al 56 Even though the estimated values are much lower for the HNO 2 channel, the estimated total rate constant for the DME + NO 2 reaction system agrees well with our calculation. Furthermore, the model proposed by Ye et al 9 is updated with our calculations on DME and NO 2 ; the updated model can better predict the experimental data, and an example of the comparison for a high NO 2 concentration is shown in Figure S5. The branching ratio of the cis-HONO channel decreases with increasing temperature, but it is still above 0.40 in the whole investigated temperature range.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 In Figure 7c, the calculated rate constants are compared with the values estimated by Xiao et al 56 Even though the estimated values are much lower for the HNO 2 channel, the estimated total rate constant for the DME + NO 2 reaction system agrees well with our calculation. Furthermore, the model proposed by Ye et al 9 is updated with our calculations on DME and NO 2 ; the updated model can better predict the experimental data, and an example of the comparison for a high NO 2 concentration is shown in Figure S5. The branching ratio of the cis-HONO channel decreases with increasing temperature, but it is still above 0.40 in the whole investigated temperature range.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The emission of nitrogen oxides (NO x ) poses an environmental problem concomitant with combustion in conventional internal combustion engines. In order to lower the level of NO x emission, advanced combustion technologies and clean alternative fuels are of intensive interest. Among the advanced combustion technologies, the exhaust gas recirculation technique has been widely used to control the temperature of in-cylinder combustion, which consequently decreases the level of NO x emission. However, the recirculated NO x , which has a 5–15% molar fraction in the exhaust gas, affects the chemical kinetics of combustion. ,, Furthermore, some nitrogenous biofuels also produce NO x in their combustion. , Therefore, considerable efforts have been devoted to the effects of NO x on the combustion of hydrocarbon fuels, such as syngas, , natural gas, , and alkanes. , These studies have demonstrated that direct hydrogen abstraction reaction from hydrocarbons by NO 2 is significant for combustion in the presence of NO x .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate constants are estimated from the values of hydrogen abstraction reactions from CH 3 OH by HO 2 radical . In addition, previous studies demonstrated that in the C/H/O/N system, hydrogen abstraction by NO 2 plays an important role in fuel oxidation at low‐to‐intermediate temperatures . Hence, the hydrogen abstraction reactions for CH 3 NHCH 3 /NO 2 are also added, and the rate constants are estimated from those of CH 3 NHCH 3 + NH 2 reactions .…”
Section: Kinetic Models and Analysesmentioning
confidence: 99%
“…For ethane, the proportion of C 2 H 5 O produced by C 2 H 5 reacting with NO 2 is low, which makes the amount of C 2 H 5 O further producing CH 2 O less, which leads to the weaker effect of NO 2 on ethane generating free radicals than methane. Ye et al 17 conducted an experimental study on the influence of NO 2 on the ignition characteristics of dimethyl ether in a shock tube. The result shows that NO 2 could promote the ignition of dimethyl ether, and with the increase of NO 2 concentration, the decreased range of ignition delay time increases.…”
Section: Introductionmentioning
confidence: 99%